Storage effects on the quality of pasteurized goat milk: Physicochemical and microbiological perspectives - Prayitno, Edi; Agung Purnomoadi; Endang Purbowati; Rudy Hartanto (Universitas Slamet Riyadi Surakarta, 2026)
This study aimed to examine the effects of storage on the physicochemical and microbiological quality of pasteurized goat milk. Milk from 40 crossbred Saanen goats, each in their third lactation period and DIM 60 (day in milk), was collected in the morning, resulting in a composite sample of 20 L. The milk was then pasteurized using the low-temperature long-time (LTLT) method. The experimental design was a completely randomized design with a factorial pattern. The treatments combined two factors: temperature and time. The temperature factor (T) consisted of T1 = room temperature (25–30°C), T2 = 15–20°C, T3 = 5–10°C, and T4 = -5–0°C. The time factor (V) consisted of V1 = 8 hours, V2 = 24 hours, and V3 = 72 hours, resulting in 12 treatment combinations (4x3) with three replications, yielding a total of 36 experimental units. The results showed a significant interaction (P<0.05) between temperature and storage time on the physicochemical and microbiological parameters of pasteurized goat milk. The total plate count (TPC) values for treatments T1V1, T1V2, and T1V3 were higher, whereas for treatments T4V1, T4V2, and T4V3, they were lower. The T0 treatment could only maintain milk quality up to 8 hours, T1 could maintain milk quality up to 24 hours, while the quality of milk in T3 and T4 treatments remained good even after 72 hours of storage. It is concluded that storage without refrigeration can maintain milk quality for up to 8 hours, while cooling with ice gel can maintain milk quality for up to 24 hours. For storing pasteurized goat milk for more than 24 hours or up to 72 hours, it is recommended to use a cooling device with a temperature below 10°C, such as a refrigerator or freezer.